1989
DOI: 10.1136/thx.44.7.601
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive respiratory failure in cicatricial pemphigoid.

Abstract: A 20 year old woman died of respiratory failure due to cicatricial pemphigoid ofthe trachea and bronchi. This is the first case with the lower airways affected to be reported.Cicatricial pemphigoid, or benign mucus membrane pemphigoid,'2 is a chronic bullous disease primarily affecting mucus membranes and less frequently the skin. It occurs from the second to the eighth decade of life, but is more common in the elderly. Its course is usually benign, though conjunctival scarring may cause visual impairment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Review of the literature revealed only 2 previous reports in which an association between MMP and lower airway (bronchial) stenosis had been suspected. 5,6 The patients described in these reports also were young (aged 22 and 20 years); however, biopsies of an affected bronchus in each case failed to demonstrate immunohistochemical changes consistent with MMP. In contrast, immunofluorescence studies performed on bronchial, skin, and conjunctival specimens obtained from the patient described herein did reveal the presence of IgG and IgA antibodies within the BMZ.…”
Section: Discussionmentioning
confidence: 82%
“…Review of the literature revealed only 2 previous reports in which an association between MMP and lower airway (bronchial) stenosis had been suspected. 5,6 The patients described in these reports also were young (aged 22 and 20 years); however, biopsies of an affected bronchus in each case failed to demonstrate immunohistochemical changes consistent with MMP. In contrast, immunofluorescence studies performed on bronchial, skin, and conjunctival specimens obtained from the patient described herein did reveal the presence of IgG and IgA antibodies within the BMZ.…”
Section: Discussionmentioning
confidence: 82%
“…Bronchoscopy performed during the exacerbation revealed severe oedema and prominent ulcer formation, which may have caused the rapid lethal outcome. Thus, 3 of the 4 cases died of the disease, indicating that the tracheal and bronchial lesions are negative prognostic factors (2)(3)(4). Reports of MMP with tracheal and bronchial lesions are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the 3 cases died. In the 2 cases, biopsies from the trachea showed subepithelial bulla (2,4). In one case, necropsy revealed the lesions on the mucosae, including the oral cavity, cornea, conjunctivae and vulva, as well as in the respiratory tracts from the larynx to small bronchi (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP includes the autoimmune diseases previously called epidermolysis bullosa acquisita, linear IgA dermatosis, and cicatricial pemphigoid with predominant MM involvement. Some MMP localizations engender major morbidity, including ocular damage and oesophageal stenosis, or, more rarely, they can cause death by laryngeal or tracheal stenosis 1–4 . For these severe cases, which represent 20–30% of all forms, 1 immunosuppressive agents are prescribed, especially cyclophosphamide (CYC), with or without corticosteroids, or intravenous immunoglobulin 1,5–7 .…”
mentioning
confidence: 99%